Characterization And Reults Test of 10 Genotypes of Gambas Plant (Luffa acutangula (L.) Roxb.) - Firrizqi, Rivana Alsya; Septia, Erfan Dani; Machmudi; Wijaya, Wahyono (Universitas Muhammadiyah Malang, 2023)
The ridge gourd plant (Luffa acutangula L.), native to India, thrives in Southeast Asian countries, including Indonesia, and holds significant value in traditional medicine. This study, conducted from September to December 2022 on PT Aditya Sentana Agro's experimental land, aimed to identify superior genotypes with high yield potential for ridge gourd production. Employing a Completely Randomized Group Design with one factor (genotype) and three replications, the research focused on qualitative (e.g., stem and leaf characteristics, flower and fruit attributes) and quantitative variables (e.g., leaf width, stem dimensions, flowering and harvest age, fruit dimensions, weight, yield, and storability). Notable findings include variations in fruit skin color as a qualitative trait. In terms of quantitative traits, certain variables such as leaf width, male flowering age, harvest age, fruit diameter, fruit length, and weight per fruit did not exhibit significant differences among genotypes. To enhance ridge gourd production, the study suggests the development of varieties with high yields and early maturation. This could contribute to the plant's adaptability in both highland and lowland environments. The comprehensive evaluation of qualitative and quantitative traits provides valuable insights for selecting the best candidate varieties to improve ridge gourd cultivation and productivity.